Pengaruh Manajemen Laba dan Transfer Pricing Terhadap Praktik Penghindaran Pajak - Syafiq Imam Hidayanto; Gia Kardinna Prima Amrania (CV. ITTC INDONESIA, 2024)
This study aims to analyze the effect of earnings management and transfer pricing on tax avoidance practices. This study uses quantitative type research methods with mining sector companies listed on the Indonesia Stock Exchange for the 2019-2020 period. The research findings show that there is a phenomenon that some mining sector companies are suspected of practicing transfer pricing in tax haven countries and the large contribution of mining sector companies to the national economy. This study uses secondary data with multiple linear analysis regression analysis methods. The sampling technique used in this study was purposive sampling with a sample of 74 samples consisting of 21 mining companies from the 2019-2022 period. The results showed that earnings management has a significant negative effect on tax avoidance practices. Transfer pricing has a negative and insignificant effect on tax avoidance practices. The difference in the results of this study is thought to be caused by differences in research places. Differences in research places will cause differences in economic conditions and differences in tax regulations. Simultaneous test results show that earnings management and transfer pricing simultaneously have a significant effect on tax avoidance practices.